A Review of the Nonpressor and Nonantidiuretic Actions of the Hormone Vasopressin - Mavani, Gaurang P.; DeVita, Maria V.; Michelis, Michael F. (Frontiers in Medicine, 2015)
The pressor and antidiuretic actions of arginine vasopressin (AVP) have been well documented. This review focuses on the less widely appreciated actions of AVP which also have important physiologic functions and when better understood may provide important insights into common disease states. These actions include effects on pain perception and bone structure as well as important relationships to the varied components of metabolic syndrome. These include effects on blood glucose, lipid levels, and blood pressure. AVP may also play a role in the progression of chronic kidney disease and effect physiologic changes relating to aging, abnormal social behavior and cognitive function. Important cellular responses including cell proliferation, inflammation and control of infection and their relationship to AVP are described. Finally, the effects of AVP on hemostasis and the hypothalamic-pituitary-adrenal access are noted. The goal of this summary of the various actions of AVP is to direct attention to the potential benefits of research in these underemphasized areas of importance.